English Language Translation through Students' Opinions Toward Google Translate Machine in the EFL Class - asti gumartifa; Sri Yuliani; Sherly Marliasari; Muhammad Tarmizi (Universitas Negeri Semarang, 2022)
The significant improvement of technology, creates the process of learning English language easier especially for students majoring in English education study program. Translation is one of the courses that utilizes Google Translate machine or technology. There were thirty-four of final semester students were selected as participants in this study. Questionnaire and interview were the instruments used in obtaining the data. There were seventeen questions of the questionnaire in order to find out students' opinions regarding to the use of Google Translate. The purpose of questions to know students’ desire to utilize Google Translate, to find out the students’ frequency of using Google Translate, and students’ agreement or disagreement to the benefits of Google Translate. This study used descriptive qualitative analysis. Half of the participants used Google Translate to support their English language learning process. Students realized some weaknesses from Google Translate, then half of students also had perception that they were still lack of confidence when they have not double-checked the appropriate meaning or target language by using Google Translate. Thus, for further English foreign language learners should understand some weaknesses of Google translate words result then eliminate those words error result in order to get good English language translation.